2018
DOI: 10.3390/fluids3020031
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Fluid Analysis of Cold Plasma Methane Reformer

Abstract: One of the most important methods of methane utilization is the conversion to synthesis gas (syngas). However, conventional ways of reforming methane usually require very high temperature, therefore non-thermal (non-equilibrium) plasma methane reforming is an attractive alternative. In this study, a novel plasma based reformer named 3D Gliding Arc Vortex Reformer (3D-GAVR) was investigated for partial oxidation of methane to produce syngas. The tangential input creates a vortex in the plasma zone and an expand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Other plasma studies have also shown satisfactory results with computational fluid dynamics modelling, such as a cold plasma methane reformer reactor in which a 3D gliding arc vortex reformer is investigated [24]. The effects of geometry and confirmation on the reformer performance for partial oxidation of methane to produce syngas are simulated.…”
Section: Introductionmentioning
confidence: 96%
“…Other plasma studies have also shown satisfactory results with computational fluid dynamics modelling, such as a cold plasma methane reformer reactor in which a 3D gliding arc vortex reformer is investigated [24]. The effects of geometry and confirmation on the reformer performance for partial oxidation of methane to produce syngas are simulated.…”
Section: Introductionmentioning
confidence: 96%
“…In large-scale applications with industrial interest, Sobhansrbandi et al [4] investigated methane reformation with cold plasma. The conversion of methane to syngas (hydrogen and carbon monoxide) was found to be economically feasible, taking advantage of the vortex flow created by a smart design of the reformer.…”
mentioning
confidence: 99%